Beneath the waves the life and navy of Capt. Edward L. Beach Jr. - Finch, Edward F. (Naval Inst. Press, 2010)
"The U.S. Navy's best known submarine officer, Capt. Edward L. Beach, enjoyed fame both as a bestselling author and as a highly decorated naval officer. Not long after the success of his first novel Run Silent, Run Deep, which was later made into a major feature film, he commanded the first submarine to circumnavigate the globe submerged. During World War II, Beach earned ten decorations for gallantry, including the Navy Cross, while on twelve combat patrols in the Pacific. Following the war, he became the public face of the submarine community and served as an aide to the first chairman of the Joint Chiefs of Staff and to President Dwight D. Eisenhower. All the while, he continued to write books, a total of ten, including three novels, before his death in 2002. This biography tells the story of Beach's remarkable life, weaving together his joint careers and offering insights into his experiences at sea and in the White House and on Capitol Hill."--Publisher's description
Includes bibliographical references (p. [239]-250) and index
Part I : 1918-1941 -- Part II : 1941-1945 -- Part III : 1945-1953 -- Part IV : 1953-1957 -- Part V : Run silent, run deep -- Part VI : 1957-1958 -- Part VII : 1958-1961--Triton -- Part VIII : 1961-1966 -- Part IX : 1966-2002 -- Appendix I : A brief chronology of the life of Edward L. "Ned" Beach Jr. -- Appendix II : Chronological bibliography of the published writings of Edward L. Beach Jr. -- Appendix III : Brief biographies of Beach family members
Keywords: Beach, Edward L. / (Edward Latimer) / 1918-2002; Beach, Edward L. -- 1918-2002; United States / Navy / Officers / Biography; United States / Navy / Submarine forces / Biography; USA; Biografie